Pe marginea fenomenului polonez de avangardă în lumina revistei „Contimporanul” - Hryhorowicz, Zdzisław (Studia Romanica Posnaniensia, 2014)
The present article is meant to offer a view of the avant-garde movement initiated by the Romanian avant-garde journal Contimporanul at the beginning of last century with regard to the Polish echoes in its pages. Together with the artistic phenomena quoted by the editors of journal, in order to offer a complete range of data, we intend to present to the Romanian public an accurate image of the Polish literary and artistic phenomenon.